Effects of water pH on gamete activation, embryonic development, and larval normality in Prochilodus lineatus - Sanches, Eduardo Antônio [UNESP]; Neumann, Giovano; De Toledo, César Pereira Rebechi; Bombardelli, Robie Allan [UNESP] (Universidade Estadual de Londrina, 2015)
We investigated the effects of breeding water pH on the spermatic motility, artificial fertilization, and initial development of offspring in curimba, Prochilodus lineatus. After hormonal induction, we conducted gamete activation, artificial fertilization, and embryo incubation in water with pH values of 4.43 ± 0.13, 5.82 ± 0.14, 7.37 ± 0.10, 8.21 ± 0.06, and 9.57 ± 0.16. When the water pH was 6.65, spermatic motility was maintained for =25.21 s (P < 0.05). The highest fertilization rates (P < 0.05) were obtained when the water pH ranged from 5.82 ± 0.14 to 8.21 ± 0.06, and the highest hatching rates (P < 0.05) were observed when the water pH was 7.37 ± 0.10. A water pH of between 7.37 ± 0.10 and 8.21 ± 0.06 resulted in more complete formation of the perivitelline space (P < 0.05); additionally, embryos incubated in alkaline waters produced a higher percentage of normal larvae (P < 0.05), despite increased mortality levels. Our results indicate that the pH of the water used for gamete activation, artificial oocyte fertilization, and incubation of eggs and larvae of P. lineatus should be ~7, in order to promote successful breeding and normal larval production.
Keywords: Artificial reproduction; Curimba; Fertilization; Fish; Sperm motility; Water pH